Developing a TPACK-Based Question Bank For Biology Education Comprehensive Exam - Adlini, Miza Nina; Jayanti, Ummi Nur Afinni Dwi; Hardiansyah, Dadang; Tanjung, Indayana Febriani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Comprehensive exams are administered to assess the abilities and knowledge of students in their respective scientific disciplines. However, the material's scope is quite extensive, particularly in light of the absence of a question bank or grid-based guide. However, advancements in the twenty-first century necessitate that educators possess not only knowledge of subject matter and the learning process but also proficiency in technology. TPACK (Technological Pedagogical Content Knowledge) refers to the amalgamation of stated components. The objective of this research is to develop a valid and practical question bank for biology education comprehensive exam, utilizing the TPACK framework. Research and development (R&D) was employed in accordance with the ADDIE development model. The instruments were validation sheets to determine the validity of the developed question bank and response questionnaires to assess its practicality. The validation sheet was intended for experts in learning evaluation and TPACK, whereas the response questionnaire was intended for students and examining lecturers who delivered comprehensive exams. The research findings indicated that the TPACK-based comprehensive exam question bank that was created exhibited a very high level of validity, as confirmed by 87.92% of learning evaluation experts and 88.69% of TPACK experts. The practicality test yielded a 91.68% passing rate among the examining lecturers and a 96.04% passing rate among the students. This value falls under the category of being extremely practical. Hence, it can be inferred that the developed question bank possesses validity and utility. This question bank aims to assist in preparing comprehensive exams for both students and lecturers, while also serving as a guide for developing TPACK, specifically designed for graduating students in the biology education program